The Inclusion of Life Skills in Secondary School English Textbooks in Saudi Arabia - Dr. Thuraya Al Jar (Journal of Educational and Human Sciences, 2021)
The ultimate goal of education is to enable people from life skills which help them to fitting for living in 21st century. Therefore, infusing life skills within the materials of the school curricula such as English student's textbook is an important issue to fulfill such goal. Yet, the purpose of this study was to find out the life skills in the content of the Saudi Student's Secondary School English Textbooks according to an inventory of the life skills which is developed by the researcher herself. To this end, an Inventory of the life skills, and a checklist of content analysis were developed and conducted to a sample consisted of 73 reading texts which were selected from a population consisted of the Saudi Student's Secondary School English Textbooks for the 4th -grade up to the 6th-grade (i.e. MGSs). Results of the study revealed that a total of (70) life skills, distributed among (10) main categories (MCs) and (25) sub-categories (SCs), were found as a result of the completely consensus among the panel of experts. Also the results revealed that all life skills of the supposed inventory were included within the analyzed textbooks. Yet, the distribution of these skills was somehow unbalanced and insufficient. Based on the study's results some recommendations were recommended.